Renewing the potential of rice crop residues as value-added products in the cosmetics industry (2024)
ABSTRACT: Purpose of this study is to explore the extraction of potentially valuable cosmetic ingredients from rice crop residues, aiming to mitigate their environmental impact. Methods: We employed AOAC methods to analyze the fat, protein, ash, fiber, soluble, and insoluble carbohydrate content in these residues. To identify sugars rich in galactose and acidic sugars, a total soluble carbohydrate extraction was performed. Cellulose, as part of the insoluble carbohydrates, was isolated through alkaline and acid hydrolysis, while sodium silicate was derived from the ash. Characterization of insoluble cellulose and silicate involved techniques like FTIR, DSC, PXRD, microphotography, porosity assessments, and water absorption studies. For proteins, alkaline solubilization and precipitation at the isoelectric point were utilized, with quantification via BCA and amino acid profiling through gas chromatography. Evaluation of radical scavenging capacity using DPPH led to the calculation of apparent molecular weight via SDS-PAGE. Results: The results revealed low levels of gum, mucilage, and pectin in both residues, contrasting with a high concentration of insoluble polysaccharides. Among these, Iβ cellulose displayed potential attributes for cosmetic applications due to its oil and water adsorption characteristics. However, silicates obtained from the ashes did not exhibit direct use potential. In terms of protein extraction, we observed antioxidant properties, with enhanced performance through enzymatic hydrolysis, achieving a hydrolysis degree of 30.41% and a DPPH radical absorption rate exceeding 70%. Conclusion: Rice residues, particularly husk and straw, shown valuable substances suitable for potential cosmetic applications, encompassing cellulose, hydrolyzed proteins, and ash as a silicate precursor.